2019
DOI: 10.1002/jcp.28197
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of oncostatin M receptor regulates local immune response in glioblastoma

Abstract: Glioblastoma (GBM) is the most lethal cancer in central nervous system. It is urgently needed to look for novel therapeutics for GBM. Oncostatin M receptor (OSMR) is a cytokine receptor gene of IL‐6 family and has been reported to be involved in regulating GBM tumorigenesis. However, the role of OSMR regulating the disrupted immune response in GBM need to be further investigated. Three gene expression profiles, Chinese Glioma Genome Atlas (CGGA), The Cancer Genome Atlas (TCGA), and Gene Expression Omnibus (GEO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Consistent with this result, bioinformatics analysis revealed that high OSMR expression indicated poor survival for glioblastoma patients [28]. In a more recent study, OSMR was found to contribute to local immune response and extracellular matrix progress in GBM and was an independent predictive factor for progressive malignancy and prognostic marker in the response prediction to radiotherapy and chemotherapy [29]. In this study, we found the antisense RNA of OSM was an independent risk factor for patient survival.…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with this result, bioinformatics analysis revealed that high OSMR expression indicated poor survival for glioblastoma patients [28]. In a more recent study, OSMR was found to contribute to local immune response and extracellular matrix progress in GBM and was an independent predictive factor for progressive malignancy and prognostic marker in the response prediction to radiotherapy and chemotherapy [29]. In this study, we found the antisense RNA of OSM was an independent risk factor for patient survival.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies demonstrated immune cell infiltration in the brain of patients with malignant glioma, although it was previously considered as an immune-privileged organ [39,40]. However, tumor-derived factors suppressed immune responses of these cells [41]. Previous studies showed that tumor-residing glioma cells regulate the immune response through recruitment of immune-suppressive cells, which represents a challenge in the development of cell immunotherapies [42].…”
Section: Discussionmentioning
confidence: 99%
“…The association between the polymorphism of OSMR gene and bladder cancer was determined, which would affect the recurrence rate, overall survival and tumor grade [17]. Xu et al have discovered that OSMR might be a prognostic biomarker in glioblastoma and overexpression of OSMR can regulate the immune response of glioblastoma [18,19].…”
Section: Discussionmentioning
confidence: 99%